Delivery Process Of Inbound Goods During The Supply Chain From Fulfillment Centers - R Punniyamoorthy; R Arulmoli (International Journal of Supply Chain Management, 2020)
Abstract - Security in the worldwide supply chain could really compare to ever. Driven by dangers, for example robbery, and burglary, it is likewise progressively muddled. It is important to advance opportune and proficient stream of genuine business while shielding and verifying the supply chain from abuse, and decreasing its helplessness to interruption. By far most of the misfortunes are owing to retail burglary. This makes retail robbery one of the most serious issues confronting independent company retailers today. The environment, atmosphere and flow of work in the FC were enchanting and cheerful which thus made the work effortless. Initial weeks were about understanding the core elements of the fulfillment centers and also understanding the operational aspects of the company and importantly the flow of the operational process